Pengaruh gandaan EDFA terhadap prestasi rangkaian cincin metropolitan - Mohammad Syuhaimi Ab-Rahman; Iskandar Yahya; Suliana Sulaiman; Sahbudin Shaari; Kasmiran Jumari (2010)
The main objective of the simulatin study is to observe the effect of gain profil for pre-amplifier and post amplifier to the output power and bit error rate (BER) performance in 600 parameter metropolitan ring network. Four profil have been introduced (A, B, C and D) and the effect of the gain value can be seen through the maximum achievable node. The study focuses also the effect of pre-amplifier on the exciting point in evaluation the BER performance. The outcomes of this study is to acquire the ideal gain value for pre and post amplifier in Optical Cross Add and Drop Multiplexer (OADM) metropolitan ring network. The Opti_System simulation is used to achieve the objectives as mentioned earlier